Hubungan Status Gizi dengan Usia Menarche Siswi Kelas VII Dan VIII - Evalina Fajriani; Diah Ulfa Hidayati; Elvina Anggraini (Jurnal Kebidanan, 2023)
Menarche is the first menstruation, usually occurring between the ages of 10-16 years or in early adolescence in the middle of puberty before entering the reproductive period. Intake of nutrients, especially fat, in the body in a certain amount or exceeding individual needs influences the start and continuation of menstruation. The aim of this study was to identify the relationship between nutritional status and age of menarche for students in grades VII and VIII at MTs NW Pengadang. The method used in this research is an analytical observational method with a cross-sectional approach. Sampling used a non-probability sampling technique with a purposive sampling method. The sample used was 40 female students from grade VII and VIII MTs. The dependent variable is menarche and the independent variable is nutritional status. The type of analysis is univariate and bivariate analysis using the Chi-Square test. The study result showed that there was a relationship between nutritional status and age of menarche for students in grades VII and VIII at MTs NW Pengadang with p-value = 0.000.